(untitled) (Update Dental College Journal, 2017)
Deep neck infection is an infection in the potential spaces and fascial planes of either with abscess formation or cellulitis .However some of may still result in fatal complications. This paper described the etiology of deep neck infection, their predisposing factors and microbial pattern. More than 50% subject of this study were of younger age group ( below 40 years) with male predominance (65%). Regarding the neck space submandibular space was the most commonly involved(32%). Etiology of neck abscess showed that odontogenic cause was the most common (60%) among the respondent, then come infected cyst, tumour. Among the predisposing factors of deep neck infection, Anaemia comprises the highest percentage (45.2%). Then comes diabetes and Liver disease, Oral hygiene, index relates with the odontogenic cause. Among the odontogenic cause patient (71.8%) had poor oral hygiene index. Regarding microbial pattern streptococcus was the highest predominance followed by Staphylococcus and E coli. This results correlates with the common dental infective microorganism which also stands for odontogenic cause of deep neck abscess. This study concluded that maintenance of good oral hygiene can prevent deep neck abscess and their devastating effect of Bangladeshi people. Update Dent. Coll. j: 2016; 6 (2): 13-20